Concomitant use of beta-1 adrenoreceptor blocker and norepinephrine in patients with septic shock - Balik, Martin; Rulisek, Jan; Leden, Pavel; Zakharchenko, Michal; Otahal, Michal; Bartakova, Hana; Korinek, Josef (Wiener klinische Wochenschrift, 2012)
BACKGROUND: Betablockade has been shown to have cardioprotective effects in patients under perioperative stress. Besides animal model of septic shock and a small cohort of septic patients, these benefits have not been studied in septic shock patients who require norepinephrine administration. METHODS: After correction of preload, an esmolol bolus (0.2-0.5 mg/kg) followed by continuous 24 h infusion was administered in septic patients with sinus or supraventricular tachycardia (HR > 120/min). Exclusion criteria were severe LV systolic dysfunction, atrioventricular blockade and norepinephrine infusion at rates over 0.5 mg/kg/min. Monitoring with echocardiography and pulmonary artery catheter before, at 2, 6, 12, 24 h following the start and 6 h after ceasing of the esmolol drip. Patients were maintained normovolemic throughout the study and adjustments of concomitant norepinephrine infusion rates were made as required. RESULTS: Ten septic patients (mean age 54.4 ± 18.7), APACHE II 21.5 ± 6.2, CRP 275 ± 78 mg/l, procalcitonin 14.5 ± 10.1 mg/l, were given esmolol drip of 212.5 ± 63.5 mg/h at start to 272.5 ± 89.5 mg/h at 24 h. Heart rate decreased from mean 142 ± 11/min to 112 ± 9/min (p < 0.001) with parallel insignificant reduction of cardiac index (4.94 ± 0.76 to 4.35 ± 0.72 l/min/m(2)). Stroke volume insignificantly increased from 67.1 ± 16.3 ml to 72.9 ± 15.3 ml. No parallel change of pulmonary artery wedge pressure was observed (15.9 ± 3.2 to 15.0 ± 2.4 mmHg) as well as no significant changes of norepinephrine infusion (0.13 ± 0.17 to 0.17 ± 0.19 mg/kg/min), DO(2), VO(2), OER or arterial lactate. CONCLUSIONS: Saving the heart 30 beats/min did not demonstrate adverse impact on global haemodynamics in rates above 110/min. Using well titratable betablocker seems to be safe and cardioprotective in septic shock patients with high cardiac output.
Keywords: Adrenergic beta-1 Receptor Antagonists; Humans; lidé středního věku; Propanolamines; Female; propanolaminy; výsledek terapie; lidé; septický šok; Norepinephrine; Shock, Septic; antagonisté beta-1-adrenergních receptorů; ženské pohlaví; Male; Middle Aged; Treatment Outcome; noradrenalin; mužské pohlaví; kombinovaná farmakoterapie; agonisté adrenergních alfa-receptorů; Adrenergic alpha-Agonists; Drug Therapy, Combination